Modificación química de la superficie de nanocápsulas de sílice a fin de implementarlas en una matriz polimérica de polietileno de alta densidad para su uso en empaques activos (2021)
Food waste in supermarkets and homes is a growing problem, especially dairy products that are highly susceptible to lipid autoxidation processes that cause rancidity. The CIPP-CIPEM research group from the Universidad de los Andes is currently working on the design of an active oxygen scavenger package made from a polymeric matrix with silica nanocapsules loaded with linseed oil to help with this problem. In this work the process of choosing a method for the chemical modification of the nanocapsule surface and the subsequent elaboration and characterization of the nanocapsules obtained as a product of the modification is presented. The purpose of this modification of the surface is to give it an apolar character, expecting that this way the nanocapsules have a better compatibility with a high-density polyethylene matrix. For the choice of the chemical modification, a Pugh matrix was used, which indicated that a modification with 3-aminopropyl triethoxysilane (APTES) and subsequent methylation of the amine by the Eschweiler-Clarke reaction was the best option. Scanning electron microscopy (SEM) and thermogravimetric analysis (TGA) were used to corroborate the formation of the nanocapsules, these tests confirmed the formation of spherical nanocapsules with an oil loading capacity of 30% of their weight. It was possible to verify the presence of amino groups on the surface of the nanocapsules after modification with APTES and the presence of methyl groups after the methylation of the amine, for this, FTIR-ATR analysis and X-ray diffraction (XRD) were used. It was possible to propose a procedure for amino functionalization of the surface of the nanocapsules and subsequent methylation of the amine, which imparts an apolar character to it.